Resting State Connectivity Between Medial Temporal Lobe Regions and Intrinsic Cortical Networks Predicts Performance in a Path Integration Task - Izen, Sarah C.; Chrastil, Elizabeth R.; Stern, Chantal E. (Frontiers in Human Neuroscience, 2018)
Humans differ in their individual navigational performance, in part because successful navigation relies on several diverse abilities. One such navigational capability is path integration, the updating of position and orientation during movement, typically in a sparse, landmark-free environment. This study examined the relationship between path integration abilities and functional connectivity to several canonical intrinsic brain networks. Intrinsic networks within the brain reflect past inputs and communication as well as structural architecture. Individual differences in intrinsic connectivity have been observed for common networks, suggesting that these networks can inform our understanding of individual spatial abilities. Here, we examined individual differences in intrinsic connectivity using resting state magnetic resonance imaging (rsMRI). We tested path integration ability using a loop closure task, in which participants viewed a single video of movement in a circle trajectory in a sparse environment, and then indicated whether the video ended in the same location in which it started. To examine intrinsic brain networks, participants underwent a resting state scan. We found that better performance in the loop task was associated with increased connectivity during rest between the Central Executive Network and posterior hippocampus, parahippocampal cortex, and entorhinal cortex. We also found that connectivity between parahippocampal cortex and the Default Mode Network during rest was associated with better loop closure performance. The results indicate that interactions between medial temporal lobe regions and intrinsic networks that involve prefrontal cortex are important for path integration and navigation.